2009
DOI: 10.1016/j.cmpb.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of duodenal imagery in celiac disease using evolved Fourier feature vectors

Abstract: Feature extraction techniques based on selection of highly discriminant Fourier filters have been developed for an automated classification of magnifying endoscope images with respect to pit patterns of colon lesions. These are applied to duodenal imagery for diagnosis of celiac disease. Features are extracted from the Fourier domain by selecting the most discriminant features using an evolutionary algorithm. Subsequent classification is performed with various standard algorithms (KNN, SVM, Bayes classifier) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Quantitative image processing applied to capsule endoscopy can potentially be useful to assess the patchiness of disease [23][24][25][26] and improvement in mucosal appearance after institution of a gluten-free diet [10], a possible future application of our method. To validate the usefulness of our new method in cases of patchy lesions will require acquisition of endoscopic biopsies at each subimage location where L is measured.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative image processing applied to capsule endoscopy can potentially be useful to assess the patchiness of disease [23][24][25][26] and improvement in mucosal appearance after institution of a gluten-free diet [10], a possible future application of our method. To validate the usefulness of our new method in cases of patchy lesions will require acquisition of endoscopic biopsies at each subimage location where L is measured.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments with the employed feature extraction techniques have shown that these results can be further improved by employing SVM or Bayes classifiers (Hegenbart et al, 2009;Vécsei et al, 2009).…”
Section: Results Discussion and Interpretationmentioning
confidence: 99%
“…To improve the results obtained by the k-nearest neighbor classifier, we use an Ensemble classifier as described in Häfner et al (2009b); Vécsei et al (2009). This classifier aims at achieving a higher overall classification accuracy and more stable results across different image classes by combining different methods.…”
Section: Methodsmentioning
confidence: 99%
“…An automated system identifying areas affected by celiac disease in the duodenum can help to improve biopsy reliability (by indicating areas eventually affected by celiac disease), can aid to improve less invasive diagnosis techniques avoiding biopsies, and can reduce the costs of interpreting video material captured during capsule endoscopy [13]. Prior approaches dealing with the computer-aided diagnosis of celiac disease using endoscopic still images images include feature extraction based on Local Binary Pattern based operators [13], band-pass type Fourier filters [14], histogram and wavelet-transform based features as well as smoothness/sharpness measures [13]. Impact of different image capturing techniques and various pre-processing schemes has been investigated as well [15].…”
Section: Classification Of Duodenal Texture For Celiac Disease DImentioning
confidence: 99%